Pengaruh Penghasilan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan Pedesaan dan Perkotaan (PBB-P2) di Kelurahan Semampir Kota Kediri - Fathon, Mohammad Alfadia; Fauziyah, Fauziyah; Isnaniati, Siti (Jurnal Ilmiah Cendekia Akuntansi, 2022)
The purpose of this study is to see how the effect of income and awareness of taxpayers on taxpayer compliance to fulfill the Rural and Urban Land and Building Tax (PBB-P2) in Semampir Village, Kediri City. This research data was obtained from PBB-P2 realization data for 2019-2021 and answers from respondents by distributing questionnaires for PBB-P2 taxpayers in Semampir Village, Kediri City as many as 96 respondents. The number of respondents is determined as a sample through a random sampling technique and is calculated based on the solvin formula. In collecting data, this study uses collection techniques in the form of documentation and questionnaires, while in analyzing the data using instrument test methods, classical assumption test, multiple regression analysis, t test (partially), and F test (simultaneously). The results of the study indicate that the taxpayer's income variable affects taxpayer compliance, it can be proven that the sig value is at 0.002 which is not more than 0.05 and taxpayer awareness affects taxpayer compliance through the sig value is 0.000 which the value is not more than 0, 05. Keywords: Taxpayer Income, Taxpayer Awareness, Taxpayer Compliance